The Effect of Information Asymmetry on Earnings Management with Corporate Governance as Moderating Variable - Karin Karin; Evelyn Kusgianto; Yulius Jogi (Business Accounting Review, 2020)
Company performance has an impact on the company’s value. Therefore, earnings management often occurs in companies. Earning management occurs when there is information asymmetry, because management have the opportunity to prioritize their own interests over shareholders. To minimize earnings management, companies need to implement good corporate governance, which can be measured by board of commissioners’ size and audit committee’s size. The objective of this study is to investigate the role of corporate governance in the relationship between information asymmetry and earnings management. The research's objects are 32 mining companies that are listed in Indonesian Stock Exchange in 2015-2019, which have been selected by purposive sampling method. Data were analyzed using multiple regression analysis. Based on the analysis, results show that Board of Commissioners’ size does not have influence on the relationship between information asymmetry and earnings management. Meanwhile, Audit Committee’s size weakens the effect of information asymmetry on earnings management.